2018
DOI: 10.3390/ijms19082413
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Cancer-Related Newly Prognostic Factors of Oral Squamous Cell Carcinoma

Abstract: Head and neck cancer, including oral squamous cell carcinoma (OSCC), is the sixth leading malignancy worldwide. OSCC is an aggressive tumor and its prognosis has exhibited little improvement in the last three decades. Comprehensive elucidation of OSCC’s molecular mechanism is imperative for early detection and treatment, improving patient survival. Based on broadly accepted notions, OSCC arises from multiple genetic alterations caused by chronic exposure to carcinogens. In 2011, research revealed 10 key altera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
197
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(197 citation statements)
references
References 141 publications
0
197
0
Order By: Relevance
“…Oral squamous cell carcinoma is the sixth most common cancer and increasing rapidly worldwide. [8] The current conventional strategies for the treatment of OSSC include surgical resection, radiotherapy and/or cisplatin based chemotherapy. [9] Even though these multimodal strategies are effective for early stage-oral cavity cancer, 5-years survival rates are significantly lower for the patients with advanced stage-oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma is the sixth most common cancer and increasing rapidly worldwide. [8] The current conventional strategies for the treatment of OSSC include surgical resection, radiotherapy and/or cisplatin based chemotherapy. [9] Even though these multimodal strategies are effective for early stage-oral cavity cancer, 5-years survival rates are significantly lower for the patients with advanced stage-oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Solid malignant tumors, such as OSCC, have the potential for rapid and unlimited growth due to resistance to apoptosis [3]. Escape from apoptosis allows cancer cells to survive longer and accumulate mutations.…”
Section: Introductionmentioning
confidence: 99%
“…HER2(also known as C-erbB-2/ERBB2/ErbB2) plays a critical role in the cell proliferation, survival, migration, angiogenesis, and metastasis through a variety of intracellular signaling cascades such as MAPK/ERK1/2 and Pi3K/Akt (18,19).An imbalance in these pathways can lead to permanent activation (20,21). Studies have established a marked correlation between HER2 expression and the poor survival of OSCC patients (22).It has been reported that the SPINKs protein family share 50% of homology to EGF moleculeand can interact by binding to EGFR, activating EGFR downstream AKT signaling pathway, inducing epithelial mesenchymal transition (23). The SPINK6 protein is secreted and act as a functional regulator of nasopharyngeal carcinoma cells metastasis through the bound to EGFR extracellular domain (23).…”
Section: Introductionmentioning
confidence: 99%